Negotiation of administrative agreements in light of the principles of impartiality, publicity and motivation (Euro-Latin American Journal of Administrative Law, 2025)
This article critically addresses the application of the principles of impartiality, publicity, and motivation in the context of the execution of administrative agreements, instruments increasingly used by the Brazilian Public Administration. The first part discusses the principle of impartiality in light of negotiation practices, demonstrating that absolute neutrality is unfeasible when the Administration itself appears as an interested party. The article then proposes a concept of impartiality guided by the equal participation of all interested parties and the adoption of institutional mechanisms that reduce the risk of capture by private groups. The second part focuses on the principle of publicity. It argues that, beyond the formal disclosure of final acts, the active disclosure of all documents and preparatory negotiations on public portals is essential to enable social oversight and legal certainty. The third section analyzes the principle of motivation, as defined in Law No. 9,784/1999, in articles 20–22 of LINDB and in Decree No. 9,830/2019, highlighting the requirement for explicit, clear, consistent, and consequentialist reasoning. The article advocates for the motivation behind the selection of negotiating clauses, the definition/quantification of fines or discounts, and the consideration of alternatives, ensuring rationality in the decision-making process. The conclusion is that, although the principles of impartiality, publicity, and motivation maintain their normative centrality, their effective observance in administrative agreements requires interpretative adaptations.
Keywords: negotiation; administrative agreements; impersonality; publicity; motivation.